'The land question': William Temple and environmentalism. Issue 4 (July 2022) - Carrette, Jeremy
This article explores Temple's understanding of the ethics of land in Christianity and Social Order . It explores Temple's engagement with contemporary issues of land in relation to profit, ownership and invasion. It is relevant to the contemporary invasion of Ukraine and environmentalism.